Inelastic neutron scattering spectroscopy of amino acids. Issue 4 (2008) - Parker Parker, Stewart F. Stewart F.; Haris Haris, Parvez I. Parvez I.
Abstract : A combination of infrared, Raman and inelastic neutron scattering (INS) spectroscopies are used to provide complete vibrational spectra of several amino acids and dipeptides. The amino acids studied were glycine, alanine, glutamine, cysteine, methionine and phenylalanine and the dipeptides studied were Gly–Gln and Gly–Ala. The findings of this study have shown how the complementarity of infrared, Raman and INS spectroscopies can be exploited to provide complete vibrational spectra of amino acids and peptides. In particular, the strengths of INS spectroscopy are highlighted: the absence of selection rules, that hydrogenic motions are emphasised, the ready access to the low energy regime (<400 cm −1 ) and the straightforward calculation of intensities. In the future, it should be possible to apply this approach to the study of larger peptides as well as proteins.